Iphiyenia Tournavitou. The Wall Paintings of the West House at Mycenae. - Sherratt, Susan (Journal of Greek Archaeology, 2018)
This book is an exceptionally full and thorough publication by Iphiyenia Tournavitou (with some further contributions by others) of wall painting fragments from the West House at Mycenae, the westernmost of the group of four buildings that lies to the west of the Mycenae Citadel and to the south of Grave Circle B. This group consists of the House of Shields, the House of the Oil Merchant and the House of Sphinxes as well as the West House, and is sometimes otherwise known collectively as the Ivory Houses.